PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL KOOPERATIF TIPE GROUP INVESTIGATION PADA SISWA KELAS XI TKJ 1 SMK KESATRIAN PURWOKERTO - Nabila, Jauza Nur; Jaelani, Anton; Handini, Elli; Wahyuni, Priska (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2024)
Mathematics as a fundamental subject is often a scourge for some students, even though mathematics can be used as a tool to understand information, so that complex problems can be modeled using mathematics and become easier to solve. Therefore, innovation is needed in teaching methods to improve mathematics learning outcomes. One method that can be used is the group investigation type cooperative learning model. The aim of this research is to determine the improvement in mathematics learning outcomes of class XI TKJ 1 SMK Kesatrian Purwokerto students through the application of the group investigation type cooperative learning model. Increase in class learning outcomes. This is evidenced by the percentage of completeness of student learning outcomes in the pre-cycle, namely 53.84% (Very Poor), increasing in the first cycle, namely 73.07% (Medium) and increasing again to 92.30% (Very Good) in cycle II. The students' average score also increased, in the pre-cycle it was 72.5, it increased in the first cycle to 76.4 (Fair) and in the second cycle it increased to 87.9 (Very Good). Based on the increase in the average student score and the percentage of completeness of student learning outcomes, the use of the group investigation type cooperative model can improve student learning outcomes.Keywords: learning outcomes, cooperation, group investigation